Comparison of Clinical and Electromyographic Outcomes of Amnion–Methylcobalamin in Carpal Tunnel Release - Made Bramantya Karna; I Ketut Suyasa; Gede Aditya Krisna; Komang Arimbawa; Ni Made Dwita Pratiwi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Carpal tunnel syndrome (CTS) commonly requires carpal tunnel release (CTR); however, residual symptoms and incomplete nerve recovery remain unresolved. Amniotic membrane and methylcobalamin have individually demonstrated anti-inflammatory, neuroregenerative, and remyelinating effects, but their combined use as an adjuvant during CTR has not been evaluated. Objective: To compare clinical and electromyographic (EMG) outcomes between standard carpal tunnel release (CTR) alone and CTR combined with amniotic membrane and methylcobalamin in patients with CTS. Methods: A nonrandomized controlled trial conducted at Prof. Dr. I.G.N.G. Ngoerah General Hospital (January–March 2025) involving 24 CTS patients allocated to CTR alone (control, n = 12) or CTR with amniotic membrane impregnated with a methylcobalamin solution (treatment, n = 12). EMG parameters (distal motor latency, amplitude, and conduction velocity) and the Liverpool Carpal Tunnel Scoring System (LCTSS) were measured preoperatively and 4 weeks postoperatively. Paired t-tests and Wilcoxon signed-rank tests were applied (α = 0.05). Results: Both groups showed significant postoperative EMG improvement (p < 0.001). The treatment group achieved greater gains in conduction velocity (Δ = +6.48 m/s vs +4.58 m/s) and SNAP amplitude (Δ = +7.44 µV vs +4.55 µV). LCTSS improved in both groups; however, the within-group difference for the treatment arm did not reach statistical significance at 4 weeks (p = 0.083). No complications were observed. Conclusion: Combining amniotic membrane and methylcobalamin with CTR accelerates electrophysiologic recovery, although the 4-week clinical advantage was not statistically significant. This combination may benefit patients with severe or recurrent CTS; however, larger randomized controlled trials with 6–12-month follow-up are warranted.